Search for narrow diphoton resonances and for γγ+W/Z signatures in pp̄ collisions at √s = 1.8 TeV - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2001)
We present results of searches for diphoton resonances produced both inclusively and also in association with a vector boson (W or Z) using 100 pb-1 of pp̄ collisions using the CDF detector. We set upper limits on the product of cross section times branching ratio for both pp̄→γγ+X and pp̄→γγ+ W/Z. Comparing the inclusive production to the expectations from heavy sgoldstinos we derive limits on the supersymmetry-breaking scale √F in the TeV range, depending on the sgoldstino mass and the choice of other parameters. Also, using a NLO prediction for the associated production of a Higgs boson with a W or Z boson, we set an upper limit on the branching ratio for H → γγ. Finally, we set a lower limit on the mass of a "bosophilic" Higgs boson (e.g., one which couples only to γ, W, and Z bosons with standard model couplings) of 82 GeV/c2 at 95% confidence level. ©2001 The American Physical Society.